Upper body training and the triceps brachii muscle of elite cross country skiers. - Terzis, G.; Stattin, B; Holmberg, H-C (Scand J Med Sci Sports, 2006)
This study aimed at evaluating whether addition of extensive upper body training in well-trained cross country skiers induces an adaptation of the triceps brachii (TB) muscle and whether this affects performance. Muscle biopsies were obtained from TB muscle in six male elite cross country skiers before and after 20 weeks of increased upper body training. The cross-sectional area of type I and IIA fibers increased by 11.3% and 24.0%, respectively, and so did the number of capillaries per fiber (2.3-3.2) (all P<0.05). SDS-polyacrylamide electrophoresis revealed in single fibers that the number of fibers expressing myosin heavy chain (MHC) type I isoform decreased from 68.7% to 60.9% (P<0.05), MHC I/IIA isoform was unaltered, while MHC IIA fibers increased from 21.6% to 35.7% and the 4.8% MHC IIA/IIX disappeared with the training (both P<0.05). Citrate synthase and 3-hydroxyacyl coenzyme A dehydrogenase activities increased by 23.3% and 15.4%, respectively, and double poling 10 km time-trial by 10.4% (all P<0.05). The values for TB are similar to what has been demonstrated for leg muscles after exercise training. The subjects who demonstrated the largest improvement in performance exhibited the largest muscle adaptation, which, in turn, was related to the pre-maximal oxygen uptake.
Keywords: 3-Hydroxyacyl CoA Dehydrogenases; Adult; Arm; Biopsy; Citrate (si)-Synthase; Electrophoresis, Polyacrylamide Gel; Humans; Male; Muscle Fibers, Skeletal; Muscle, Skeletal; Myosin Heavy Chains; Physical Education and Training; Skiing; Statistics, Nonparametric